Desain model Sistem Teknologi Blockchain untuk Pemerataan Pembangunan di Indonesia - Harison Harison; Rusfidra Rusfidra (Lembaga Pengembangan Kinerja Dosen, 2025)
Development inequality in Indonesia remains a strategic issue, with a significant gap between the western and eastern regions. Various factors such as corruption, bureaucratic inefficiency, and lack of transparency in public fund management have undermined the effectiveness of development programs. This article proposes a blockchain-based model design as an innovative approach to enhance transparency, accountability, and efficiency in the distribution of national development funds. Through a consortium blockchain model equipped with smart contracts, every transaction can be traced in real time, while fund disbursement is executed automatically based on verified project milestones. This mechanism enables active public participation in monitoring processes while minimizing the potential for budget misuse. With an estimated initial investment of IDR 110–195 billion and potential annual savings of IDR 150–200 trillion, the system implementation promises a Return on Investment (ROI) of 1000–1500% within three to five years. The article also presents the system architecture design, business process notation for stakeholder involvement, and business process notation for community engagement in monitoring and supervising development projects implemented in their respective regions. This approach establishes transparency in the distribution of development programs from the central government to regional areas, which can be directly monitored by local communities.